2014
DOI: 10.4314/ahs.v13i4.40
|View full text |Cite
|
Sign up to set email alerts
|

Demographic profile and epidemiology of injury in Mthatha, South Africa

Abstract: Objective: To determine the magnitude, socio-demographic and epidemiological characteristics of injury at a Provincial referral hospital. Methods: This review was conducted on all trauma patients admitted at the Mthatha Hospital Complex and Nelson Mandela Academic Hospital from the 1 st January 1997 to the 31 st December 2000. Results: The incident rate of injuries was 3.2% (n=2460/75,833 total admissions). Injured patients were mostly black (80%) and males (ratio: 5 men: 1 woman). Only 8.1% of injured patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 16 publications
5
13
4
Order By: Relevance
“…Furthermore, young men living in South Africa face extremely high rates of interpersonal violence. A study assessing hospital data on injuries within the Mthatha Hospital Complex in South Africa, found that the majority of injuries occurred among men, with 60% of all cases being for acts of interpersonal violence [27]. Despite extremely high levels of PTEs within men participating in our study, we found that this was not significantly associated with increased depression symptomology or inconsistent condom use.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Furthermore, young men living in South Africa face extremely high rates of interpersonal violence. A study assessing hospital data on injuries within the Mthatha Hospital Complex in South Africa, found that the majority of injuries occurred among men, with 60% of all cases being for acts of interpersonal violence [27]. Despite extremely high levels of PTEs within men participating in our study, we found that this was not significantly associated with increased depression symptomology or inconsistent condom use.…”
Section: Discussioncontrasting
confidence: 61%
“…In South Africa, where reports of violence are known to under-estimate the true prevalence [25], 20% of women attending antenatal care reported experiencing sexual violence, among the highest prevalence in the world [22, 26]. Among adolescent men, experiences of perpetrating or witnessing interpersonal violence drive rates of trauma exposure [11, 24, 27]. This is significant as earlier research among South African adolescent men demonstrated an association between witnessing community violence and high sexual HIV risk behaviours such as multiple concurrent sexual partnerships [28].…”
Section: Introductionmentioning
confidence: 99%
“…Out of the total injured household number, males were more affected than females in the study. It is similar to other injury studies from different countries (2,3,(9)(10)(11)(12)(13) . The reason might be due to male involvement in risk taking behaviors and social interactions, which are highly correlated with injuries (14)(15)(16)(17) .…”
Section: Discussionsupporting
confidence: 90%
“…Injury was more common among individuals from household of the second-tier wealth index compared with highest tier. Different injury studies indicate low socioeconomic status as a risk factor for the occurrence of injury (12,26,32,33) . However, this current study found that the lowest wealth index was not a factor.…”
Section: Discussionmentioning
confidence: 99%
“…One: Nigerian workers highlight the issue of hearing loss with increasing age (presbycussis). 24 They report that the commonest symptoms were hearing loss, tinnitus, and vertigo. Hearing impairment affected both speech and higher frequencies.…”
Section: Nodding Syndrome (Ns) Still An Enigmamentioning
confidence: 99%